2017
DOI: 10.1186/s12889-017-4220-0
|View full text |Cite
|
Sign up to set email alerts
|

Does parental and adolescent participation in an e-health lifestyle modification intervention improve weight outcomes?

Abstract: BackgroundFew studies have evaluated the effect of adherence to a lifestyle intervention on adolescent health outcomes. The objective of this study was to determine whether adolescent and parental adherence to components of an e-health intervention resulted in change in adolescent body mass index (BMI) and waist circumference (WC) z-scores in a sample of overweight/obese adolescents.MethodsIn total, 159 overweight/obese adolescents and their parents participated in an 8-month e-health lifestyle intervention. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…While this is the first known study targeting parents of children with a mobility disability, a small but growing number of studies have been published examining feasibility and preliminary behavior change outcomes among parents with children with other conditions including cancer, mental health conditions, substance abuse, and chronic kidney disease. [38][39][40][41][42] In many of these studies, parents reported acceptability of the web-based interventions and many noted they found the material helpful, but none have reported significant change in parental or child behavior. This underscores the need to find digital interventions that are beneficial in providing resources and supporting engagement, while balancing the time constraints and mental fatigue experienced by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…While this is the first known study targeting parents of children with a mobility disability, a small but growing number of studies have been published examining feasibility and preliminary behavior change outcomes among parents with children with other conditions including cancer, mental health conditions, substance abuse, and chronic kidney disease. [38][39][40][41][42] In many of these studies, parents reported acceptability of the web-based interventions and many noted they found the material helpful, but none have reported significant change in parental or child behavior. This underscores the need to find digital interventions that are beneficial in providing resources and supporting engagement, while balancing the time constraints and mental fatigue experienced by caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The ACAES has been validated in a sample of 224 students aged between nine and 16 years from the Hunter region in NSW, reporting validity coefficients of 0.21 and 0.24 for energy and sugar respectively when compared with assisted food records (Watson et al, 2009). The ACAES will be Parents will receive six fortnightly notifications in the second term via the school's electronic communication channel (Head et al, 2013;Sharifi et al, 2013;Tu et al, 2017). The notifications will provide advice on reducing SSB consumption and availability in the home environment, suggestions of healthier drink alternatives and role modelling (Denney-Wilson et al, 2009;Wold, 2009).…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Despite improved technologies and access to mHealth tools for the purpose of monitoring health status and implementing interventions for health behavior change [ 22 , 23 ], challenges with adherence and exposure remain [ 24 , 25 ]. Planned exposure, impact, and potential outcomes are altered by participants’ interaction with study tools and technology [ 13 , 15 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…mHealth tools provide adjunctive options to standard treatment approaches and can be beneficial for patients at home and their clinical team. However, engagement with devices and apps can act as a barrier to treatment [ 13 , 15 , 22 ].…”
Section: Introductionmentioning
confidence: 99%